A Liberation Theology of Child and Vulnerable Adults’ Safeguarding: The Case of the Society and the Church of Burkina Faso. (Hekima Review, 2022)
The Good News of Jesus Christ has reached out to the people of Burkina about one hundred years ago. However, for this Gospel to take deeper roots and transform the people of this country there is a need of checking out the bad treatment of a big part of the people of God (children and vulnerable adults) in our society and Church and ban them. Even if from the outset the local Church has fought the abuse of young girls’ mistreatment as well as their forced-wedding, yet until now there is need for more deep actions in this area to protect not only girls’ rights but mainly the one of all children and vulnerable adults in respect to Christ’s respect for all human beings particularly for the little ones, the vulnerable. How to challenge neglect and superficial handling of abuse of vulnerable and minors’ abuse particularly in the Church and society at large in Burkina? This is what the article will try to answer calling it an effective liberation of our way of preaching the Gospel.